Comment l'impératif écologique aliène les femmes - Bouazzouni, Nora (Slate.fr, 2019)
Qu'elles soient du Sud ou du Nord, les femmes subissent le changement climatique ou les injonctions qui en découlent. C'est à se demander si féminisme et écologie sont compatibles.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; com5170; communication; cours; discipline; environnement; féminisme pop; journalisme; premier cycle; périodes historiques; thématiques; écoféminisme; écologie

Dénoncer les féminicides des femmes autochtones aux États-Unis et au Canada La bande dessinée Deer Woman d’Elizabeth LaPensée, une super-héroïne autochtone éco-féministe ? - Bonadè, Sophie; Hamus-Vallée, Réjane; Journée-Duez, Aurélie (Genre en séries, 2019)
À travers l’analyse de la bande dessinée Deer Woman créée en 2015 par Elizabeth LaPensée (Anishinaabe, Canada), notre article a pour objectif principal d’interroger la notion de « super-héroïne » à l’aune de représentations autochtones engagées. Il s’agit de voir en quoi cette revitalisation du mythe traditionnel de la Femme Cerf (Deer Woman) interroge l’identité en termes de sexe et de genre, la culture et la place des femmes autochtones, en prenant une position radicale face au problème sociétal des féminicides en Amérique du Nord. Nous postulons que la figure de Deer Woman peut aussi être vue aujourd’hui comme une allégorie mettant en garde contre la domination masculine sur les femmes et sur toutes autres formes de vie. Tout d’abord, nous étudierons les caractéristiques formelles de Deer Woman et les mythes fondateurs autochtones qui en sont à l’origine. Nous montrerons ensuite en quoi cette super-héroïne dont les pouvoirs apparaissent après qu’elle a été sexuellement agressée, tend à dénoncer et lutter contre les féminicides touchant les femmes autochtones. Enfin, nous nous demanderons comment cette bande dessinée pourrait laisser entrevoir l’émergence d’une super-héroïne autochtone éco-féministe.
Keywords: amérique du nord; amériques; approches et analyses; arts; bande-dessinée; cours; discipline; environnement; féminicide; féminisme autochtone; féminisme pop; histoire et politique; justice sociale; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; super-héroïnes; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Navigating, challenging, and contesting normative gendered discourses surrounding women’s pornography use - Marques, Olga (Journal of Gender Studies, 2019)
While there exists some empirical research on women’s use of pornography, the manner in which women do, and how they understand their pornographic spectatorship, remains under-examined. Focusing on the narratives of 26 women gained through both focus groups and individual interviews, this research explores how women who use pornography and other sexually explicit materials navigate, reaffirm, challenge, and contest normative gendered boundaries that surround women’s sexuality, sexual pleasure, and women’s pornographic use. While ‘pornography as female degradation’ is the most visible feminist discourse, the findings of this study suggest that the meanings attributed to both the experience of engaging with pornography, as well as with pornographic materials themselves, were far from wholly degrading, and in fact, served to provide pleasure, sexual self-actualization, and even corporeal validation – disrupting normative discourses of desiring and desirable bodies.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; corps; cours; féminisme pop; ontario; premier cycle; périodes historiques; régions géographiques; sex1911; sexualité; thématiques

Trente - Darsigny, Marie (Les éditions du remue-ménage, 2018)
Trente, un nombre qui n’arrivera jamais et s’il arrive, je l’éviterai, comme j’ai une fois évité un chevreuil en conduisant sur la route, le chevreuil courait devant mon auto, à gauche il y avait la rivière et à droite il y avait le fossé, c’est beau la Montérégie, au lieu de choisir l’un ou l’autre il continuait d’avancer droit devant, puis il a fini par bondir vers le fossé. Moi j’aurais choisi l’eau et d’ailleurs, à chaque fois que j’empruntais ce chemin-là, ça me chicotait de savoir que juste un petit coup de volant pouvait m’envoyer dans la rivière, un jour on est en vie et un jour on ne l’est plus, c’est tout.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discours dominant; fem3500; féminisme pop; premier cycle; périodes historiques; québec; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

You play the girl: on Playboy bunnies, Stepford wives, train wrecks, and other mixed messages - Chocano, Carina (Houghton Mifflin Harcourt, 2017)
"Who is "the girl"? Look to movies, TV shows, magazines, and ads and the message is both clear and not: she is a sexed-up sidekick, a princess waiting to be saved, a morally infallible angel with no opinions of her own. She's whatever the hero needs her to be in order to become himself. She's an abstraction, an ideal, a standard, a mercurial phantom. In You Play the Girl, Chocano blends formative personal stories with insightful and emotionally powerful analysis. Moving from Bugs Bunny to Playboy Bunnies, Flashdance to Frozen, the progressive '70s through the backlash '80s, the glib '90s, and the pornified aughts--and at stops in between--she explains how growing up in the shadow of "the girl" taught her to think about herself and the world and what it means to raise a daughter in the face of these contorted reflections. In the tradition of Roxane Gay, Rebecca Solnit, and Susan Sontag, Chocano brilliantly shows that our identities are more fluid than we think, and certainly more complex than anything we see on any kind of screen."--Page 4 of cover.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; représentation des femme*; sofia; systèmes d'oppressions; thématiques

Filles - Darsigny, Marie (Les éditions de l'écrou, 2017)
Filles, c’est la plainte de celle qui quitte le bar après le last call, celle qui fixe le vide de l’hôpital jusqu’à ce que les murs ondulent, c’est l’idée entêtante que tout ira toujours plus mal, que rien ne sera salutaire, que le fond arrivera plus vite si on gratte le bobo jusqu’à en scrapper sa manucure ; c’est toutes ces petites blessures qui se font facilement et qui cicatrisent mal. ​
Keywords: amériques; approches et analyses; corps; féminisme pop; poésie; québec; régions géographiques; santé; santé mentale; thématiques; violences

Commando culotte : les dessous du genre et de la pop-culture. - Malle, Mirion (Label 619, 2016)
Game of Thrones, Legally Blonde, Sixteen Candles, Starship Troopers… Mirion Malle analyse des oeuvres marquantes du petit et grand écran sous l’angle du genre et du féminisme. Quelles places ont les femmes dans les blockbusters et les séries télé ? Quel est l’impact sur notre société ? Voilà les questions auxquelles répond Commando Culotte avec pédagogie mais aussi humour et légèreté, alternant critiques et déconstruction de mythes sexistes comme “les filles n’ont pas d’humour", “la friendzone", “le maquillage c’est nul et c’est pour les filles, les flingues c’est cool et c’est pour les garçons", et bien d’autres.
Keywords: 2000 à aujourd'hui; approches et analyses; cours; fem3500; féminisme pop; genre; identités LGBTQIA2+; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Pornography, feminist views of - Davis, Berta (The International Encyclopedia of Human Sexuality, 2015)
Feminist women's attitudes toward pornography are significantly polarized. Anti‐porn feminists have taken a position that pornography is degrading toward women, leads to distortion of healthy male‐female sexuality, leads to distorted images of the female body, increases male anxiety about sexual adequacy, sexual compulsivity, and increase violence toward women including rape and sexual harassment.
Keywords: approches et analyses; cours; discipline; féminisme anti-porn; féminisme pop; pornography; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; thématiques

The mask you live in - Newsom, Jennifer Siebel; Anthony, Jessica; Kanopy (Firme) (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, attitudes performatives, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France); Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Collection Nouvelles scènes, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Rethinking the effects paradigm in porn studies - McNair, Brian (Porn Studies, 2014)
It has been an assumption of most anti-pornography discourse that porn damages women (and children) in a variety of ways. In Porno? Chic!, the author interrogated this assumption by examining the correlation between the incidence of sexual violence and other indicators of misogyny, and the availability and accessibility of pornography within a number of societies. This article develops that work with a specific focus on the regulatory environment as it relates to pornography and sexual representation. Does a liberal regulatory regime in sexual culture correlate with a relatively advanced state of sexual politics in a given country? Conversely, does an illiberal regime, where pornography and other forms of sexual culture are banned or severely restricted, correlate with relatively strong patriarchal structures? A comparative cross-country analysis seeks to explain the correlations identified, and to assess the extent to which the availability of porn can be viewed as a causal or a consequential characteristic of those societies where feminism has achieved significant advances.
Keywords: LGBTQIA2+; analyse comparée; approches et analyses; communication; corps; cours; discipline; droits des femmes*; féminisme pop; histoire et politique; identités LGBTQIA2+; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; violences; études culturelles

The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Next wave : new directions in women's studies, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles

Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

The feminist porn book: the politics of producing pleasure - Taormino, Tristan; Shimizu, Celine Parreñas; Penley, Constance; Miller-Young, Mireille (The Feminist Press at the City University of New York, 2013)
''This book brings together writings by feminists in the adult industry and research by feminist porn scholars. It investigates not only how feminists understand pornography, but also how feminists do porn - that is, direct, act in, produce, and consume this kind of 'industry'. With contributions by Susie Bright, Candida Royalle, Betty Dodson, Nina Hartley, Buck Angel, Lynn Comella, Jane Ward, Ariane Cruz, Kevin Heffernan, and more.''-- Fourni par l'éditeur.
Keywords: approches et analyses; arts; arts visuels et médiatiques; cinéma; communication; corps; cours; discipline; féminisme pop; féminisme pro-sexe; histoire et politique; premier cycle; ressource en ligne; sciences humaines; sex1911; sex1920; sexologie; sexualité; thématiques

Femmes et médias: une image partiale et partielle - Bamberger, Clara (Inter-national, Série Premières synthèses - jeunes chercheurs : concours Sciences-Po, 2012)
Les femmes sont beaucoup moins visibles que les hommes dans les médias d'information. Les femmes, lorsqu'elles sont interviewées, le sont principalement en qualité de mères, de simples témoins ou de victimes. Sur la scène médiatique, les rôles de l'expert, de l'intellectuel ou du professionnel reste largement préemptés par les hommes. D'où vient cette représentation biaisée des sexes ?
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; europe; france; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; systèmes d'oppressions; thématiques

Féminismes et pornographie - Courbet, David (L'attrape-corps, 2012)
Comment le féminisme peut se reconnaître dans la pornographie Objet de débats où la passion l'emporte bien souvent sur la raison, la pornographie semble à première vue s'opposer au féminisme. Or, les années 1980 voient éclore aux Etats-Unis un courant se définissant comme " pro-sexe " porté par des figures telles Annie Sprinkle ou Candida Royalle. Avec l'idée que la pornographie n'est pas systématiquement condamnable, la question suivante s'impose : peut-on parler de moyen d'émancipation ? La femme doit être libre de choisir la sexualité qui lui convient. Les films pornographiques conçus par des hommes et pour des hommes ne lui permettant pas d'obtenir une satisfaction complète, des réalisatrices, parmi lesquelles Erika Lust, Ovidie ou Emilie Jouvet, promeuvent une pornographie alternative où le plaisir féminin est - enfin - mis en exergue. Et brisent les standards pornographiques dominants ! Peu étudiées en France, les thèses défendues par les féministes pro-sexe n'ont encore que peu d'échos au sein du grand public. Basé notamment sur une dizaine d'entretiens de spécialistes et professionnels, ce travail cherche à élucider en quoi le féminisme peut se reconnaître dans la pornographie. Et inversement.
Keywords: approches et analyses; corps; cours; discipline; féminisme pop; féminisme pro-sexe; journalisme; premier cycle; science politique; science politique et droit; sciences humaines; sex1911; sexologie; sexualité; thématiques; travail

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Anti-porn: the resurgence of anti-pornography feminism - Long, Julia (Zed Books, 2012)
"Anti-porn feminism is back. Countering the ongoing 'pornification' of Western culture and society, with lads' mags on the middle shelf and lap-dancing clubs in residential areas, anti-porn movements are re-emerging among a new generation of feminist activists worldwide. This essential new guide to the problems with porn starts with a history of modern pro and anti political stances before examining the ways in which the new arguments and campaigns around pornography are articulated, deployed and received. Drawing on original ethnographic research, it provides an in-depth analysis of the groups campaigning against the pornography industry today, as well as some eye-opening facts about the damage porn can do to women and society as a whole. This unique and inspiring book explains the powerful comeback of anti-porn feminism, and it controversially challenges liberal perspectives and the mainstreaming of a porn culture that threatens to change the very nature of our intimate relationships"--Résumé de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme anti-porn; féminisme pop; militance; patriarcat; premier cycle; sex1911; sexualité; systèmes d'oppressions; thématiques

Miss representation - Siebel Newsom, Jennifer; Dietrich, Claire; Costanzo, Julie; Congdon, Jessica; Roco Films Educational (Firme); Girls Club Entertainment (Girls Club Entertainment, 2011)
Like drawing back a curtain to let bright light stream in, MISS REPRESENTATION uncovers a glaring reality we live with every day but fail to see. Written and directed by Jennifer Siebel Newsom, the film exposes how mainstream media contributes to the under-representation of women in positions of power and influence in America. The film challenges the media’s limited and often disparaging portrayals of women and girls, which make it difficult for women to achieve leadership positions and for the average woman to feel powerful herself. In a society where media is the most persuasive force shaping cultural norms, the collective message that our young women and men overwhelmingly receive is that a woman’s value and power lie in her youth, beauty, and sexuality, and not in her capacity as a leader. While women have made great strides in leadership over the past few decades, the United States is still 90th in the world for women in national legislatures, women hold only 3% of clout positions in mainstream media, and 65% of women and girls have disordered eating behaviors.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; documentaire; féminisme pop; premier cycle; périodes historiques; représentation des femme*; régions géographiques; santé; sex2283; sexualité; thématiques; travail; états-unis

elles@centrepompidou Une nouvelle histoire ? - St-Gelais, Thérèse (Esse, 2010)
Commentaire de l'exposition elles@centre pompidou, Artistes femmes dans la collection du Musée national d’art moderne, centre de création industrielle qui eut lieu du 27 mai 2009 - 21 févr. 2011 au centre Pompidou à Paris.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; ressource en ligne; sofia; thématiques